2019
DOI: 10.1002/pd.5434
|View full text |Cite
|
Sign up to set email alerts
|

The uptake of pan‐ethnic expanded carrier screening is higher when offered during preconception or early prenatal genetic counseling

Abstract: Objective To examine factors that influence uptake of expanded carrier screening (ECS) among women undergoing preconception and prenatal genetic counseling. Methods We retrospectively reviewed 500 medical records from women with prenatal or preconception genetic counseling at a prenatal genetic counseling service. We tabulated acceptance of ECS by indication for genetic counseling along with demographic and pregnancy‐related factors. Results ECS was offered to 483 of 500 women, and 192 (39.8%) accepted. Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…This finding is consistent with a previous retrospective study comparing ECS actual uptake rate between pregnant and nonpregnant women. The study found significantly more nonpregnant women accepting ECS after pre-test counseling by geneticists compared to pregnant women in their 13-14 weeks of gestation (Larsen et al, 2019). When it comes to the reason for electing or declining ECS, the top reason in both groups for electing ECS was that women thought ECS is helpful in confirming whether their children were at risk of recessive genetic diseases, thereby guiding them to make informed choices.…”
Section: Discussionmentioning
confidence: 93%
“…This finding is consistent with a previous retrospective study comparing ECS actual uptake rate between pregnant and nonpregnant women. The study found significantly more nonpregnant women accepting ECS after pre-test counseling by geneticists compared to pregnant women in their 13-14 weeks of gestation (Larsen et al, 2019). When it comes to the reason for electing or declining ECS, the top reason in both groups for electing ECS was that women thought ECS is helpful in confirming whether their children were at risk of recessive genetic diseases, thereby guiding them to make informed choices.…”
Section: Discussionmentioning
confidence: 93%
“…However, the patient's gestational age ( p = .014) and parity ( p < .001) did influence if partners pursued carrier screening. These two factors have previously been described as general predictors of prenatal genetic testing uptake …”
Section: Discussionmentioning
confidence: 98%
“…These two factors have previously been described as general predictors of prenatal genetic testing uptake. 21 Due to the retrospective nature of this study, analysis was restricted to information documented in our clinical database. We could therefore not ascertain more specific predictors or barriers related to partner carrier screening uptake.…”
Section: Gjb2-related Nonsyndromic Hearing Loss and Deafnessmentioning
confidence: 99%
“…The acceptance of carrier screening is higher for couple who received genetic counselling before pregnancy. The uptake of carrier screening was 68.7% and 35.1% for couple who were counselled preconceptionally and during pregnancy, respectively 8 . Factors such as indication for genetic counselling, maternal and paternal family history of genetic diseases, maternal and paternal age, ethnicity, multigestational pregnancies, and previous miscarriages were not significantly associated with the acceptance rate of expanded carrier screening 8 .…”
Section: When Should Expanded Carrier Screening Be Offered?mentioning
confidence: 99%
“…The uptake of carrier screening was 68.7% and 35.1% for couple who were counselled preconceptionally and during pregnancy, respectively 8 . Factors such as indication for genetic counselling, maternal and paternal family history of genetic diseases, maternal and paternal age, ethnicity, multigestational pregnancies, and previous miscarriages were not significantly associated with the acceptance rate of expanded carrier screening 8 . Although the underlying cause of the difference in uptake was not identified, it was postulated that limited pregnancy options after prenatal diagnostic testing affected the willingness of couple to undergo expanded carrier screening 8 .…”
Section: When Should Expanded Carrier Screening Be Offered?mentioning
confidence: 99%